Strategic place brand management of Kuala Terengganu coastal heritage city, Malaysia - Muhamad Fazil, Ahmad (2016)
The World Trade Organization (WTO) reported that travel and tourism industry has become one of the main contributors to the economic development of the countries. In the United States alone, travel and tourism industry has approximately contributed USD 2.36 trillion in the year 2014. Realizing the importance of tourism industry towards country’s economy, many countries have passed some budget on place branding research. Place branding, one of the segments in destination branding, is a complex process of branding an entire country or a part of it. Hanna and Rowley (2011) have developed the Strategic Place Brand-Management model (SPBM-model) comprises of nine (9) dimensions which are argued to be important parts in the place branding process and research. The objectives of this research are to understand how Kuala Terengganu copes with the components in the SPBM-model, and to perceive which components in the SPBM-model that can be seen as the most important components based on the perceptions of Kuala Terengganu residents. The methodology of this study was made through a case study of the city of Kuala Terengganu. With the intention of gaining data, five semi-structured interviews were conducted with executives officers that working for developing Kuala Terengganu branding as a tourism destination. By positioning the Kuala Terengganu place branding process with the SPBM-model, it can be understood that all components are strongly connected to each other. Of all nine (9) components, three (3) of them which are evaluation, infrastructure and stakeholders should be given special attention by the Majlis Bandaraya Kuala Terengganu if they are serious in branding Kuala Terengganu as one of the most attractive tourist destinations in the world.